Bioclimatic modeling of the distribution of brown marmorated stink bug Halyomorpha halys (Stål, 1855), with special reference to Ukraine - Tytar, V.M.; Kozynenko, I.I. (Доповіді НАН України, 2020)
Due to the potential severity of the impact of brown marmorated stink bug Halyomorpha halys both in terms
of the plant susceptibility and economic loss and the border detection of the bug in the seaport city of Odesa, it is
important to determine the potential suitable bioclimatic range in Ukraine. The bioclimatic modeling suggests that,
under the current climate conditions, the pest has varying chances in the near term to invade a number of regions in
Ukraine, especially in the south of the country: Transcarpathia, Crimea, portions of Odesa, Mykola¿v, Kherson, and
Zaporizhzhya regions. Зважаючи на шкодочинність мармурового клопа Halyomorpha halys для сільськогосподарських культур і
пов'язані з цим економічні втрати, а також виявлення цього шкідника в портовому місті Одеса, важливо
визначити території в Україні, де біокліматичні умови сприятимуть його поширенню. Згідно з результатами біокліматичного моделювання, за сучасних кліматичних умов шкідник має різні шанси в найближчій
перспективі вторгнутись у низку регіонів України, особливо на півдні країни: Закарпаття, Крим, частину
Одеської, Миколаївської, Херсонської та Запорізької областей. Учитывая вредоносность мраморного клопа Halyomorpha halys для сельскохозяйственных культур и связанные с этим экономические потери, а также обнаружение этого вредителя в портовом городе Одесса,
важно определить территории в Украине, где биоклиматические условия будут способствовать его распространению. Согласно результатам биоклиматического моделирования, в современных климатических
условиях вредитель имеет разные шансы в ближайшей перспективе вторгнуться в ряд регионов Украины,
особенно на юге страны: Закарпатье, Крым, часть Одесской, Николаевской, Херсонской и Запорожской
областей.